Komunitas Peduli Pencegahan dan Penanganan Perdagangan Orang Berbasis Masyarakat - Grace Jenny Soputan; Mayske Liando; Tinneke E.M. Sumual (DEDIKASI, 2018)
Human trafficking, especially female and children, is an act that is contrary to human dignity andviolation of human rights, so it must be eradicated. Female’s trafficking in North Sulawesi Province is still highuntil 2017. Specific target of this activity is firstly, the formation of a small group concerned with the prevention andhandling of the Crime of Trafficking in Persons in the City of Bitung, especially in the 8 selected villages in MaesaDistrict. First, making these communities as agents of change in the prevention of female and children trafficking.The result achieved, the formation of 8 community groups in 8 villages in the city of Bitung in accordance with theDecree of the Maesa District Chief. Second, the community formed becomes an agent of change with the main taskof preventing the trafficking of women as both the origin and as the recipient area, or the transit area for shippingactivities.